Respiratory Infections in Children During a Covid-19 Pandemic Winter - Diesner-Treiber, Susanne C.; Voitl, Peter; Voitl, Julian J. M.; Langer, Klara; Kuzio, Ulrike; Riepl, Angela; Patel, Pia; Mühl-Riegler, Alexandra; Mühl, Bernhard (Frontiers in Pediatrics, 2021)
Background: The Covid-19 pandemic compelled the implementation of measures to curb the SARS CoV-2 spread, such as social distancing, wearing FFP2 masks, and frequent hand hygiene. One anticipated ramification of these measures was the containment of other pathogens. This prospective, longitudinal study aimed to investigate the spread of 22 common seasonal non-SARS-CoV-2 pathogens, such as RSV and influenza, among children with an acute respiratory infection during a pandemic. Methods: Three hundred ninety children (0-24 months) admitted to Vienna's largest pediatric center with acute respiratory infection (November 2020 to April 2021) were included in this study. The researchers tested nasal swabs for 22 respiratory pathogens by Multiplex PCR, documented clinical features and treatment, and evaluated data for a potential connection with the lockdown measures then in force. Results: The 448 smears revealed the most common pathogens to be rhino-/enterovirus (41.4%), adenovirus (2.2%), and coronavirus NL63 (13.6%). While the first two were active throughout the entire season, coronaviruses peaked in the first trimester of 2021 in conjunction with the lift of the lockdown period (OR 4.371, 95%CI 2.34-8.136, P<0.001). RSV, metapneumovirus, and influenza were absent. Conclusion: This prospective, longitudinal study shows that Covid-19 measures suppressed the seasonal activity of influenza, RSV, and metapneumovirus among very young children, but not of rhino-/enterovirus and adenovirus. The 0-24 month-olds are considered the lowest risk group and were only indirectly affected by the public health measures. Lockdowns were negatively associated with coronaviruses infections.